Operationalization of intersectionality in physical activity and sport research: A systematic scoping review - Heejun Lim; Eun Jung; Kaila Jodoin; XiaoWei Du; Lee Airton; Eun-Young Lee (Elsevier, 2021)
Participation in and opportunities for physical activity (PA) and sports (PA inclusively hereafter) are known to vary across individuals with different social positions. Intersectionality theory may help us to better understand the complex processes of multiple interlocking systems of oppression and privilege shaped by intersections of individuals' social categories. The objectives of this systematic scoping review were (1) to summarize the findings of articles examining PA claimed operationalization of intersectionality and (2) to identify the scope and gaps pertaining to the operationalization of intersectionality in PA research. A search was conducted in September 2019 in seven electronic databases (e.g., SPORTDiscus, Scopus, Web of Science) for relevant research articles written in English. Key search terms included "intersectionality" AND "physical activity" OR "sport". Database searches, data screening and extraction, and narrative synthesis were conducted between September 2019 and May 2020. Of 16564 articles identified, 45 articles were included in this review. The majority of included articles used qualitative methods (n = 41), with two quantitative and two mixed-methods articles. The most frequently observed intersectional social position was sex/gender + race/ethnicity (n = 11), followed by sex/gender + race/ethnicity + sexuality (n = 6) and sex/gender + race/ethnicity + religion (n = 6). Most qualitative studies (n = 38) explicitly claimed operationalization of intersectionality as a key theoretical framework, and over half of these studies (n = 27) implicitly used intra-categorical intersectionality. Two quantitative studies were identified which examined a number of intersections simultaneously using inter-categorical intersectionality. Complex processes of individual and social-structural level factors that drive inequalities in PA opportunities and participation could be better elucidated with the operationalization of intersectionality theory. Intersectionality theory may serve as a useful framework in both qualitative and quantitative investigations. Advancement in quantitative intersectionality is critical in order to produce knowledge that could inform more inclusive PA promotion efforts.